2018
DOI: 10.1080/00220388.2018.1516867
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal Gold Mining and Farming: Livelihood Linkages and Labour Dynamics after Land Reforms in Zimbabwe

Abstract: While the rural development consequences of Zimbabwe's Fast Track Land Reform Programme have been heavily debated, there is a dearth of literature focusing on the post-land reform interrelations between artisanal and small-scale gold mining (ASGM) and farming. This article discusses the growing ASGM sector, encapsulated by the phrase 'mari yaputika'/'gold has detonated', examining the impacts of 'liberating' mineral resources in farming areas previously inaccessible to the rural poor. Drawing on research in Mh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 56 publications
1
45
0
2
Order By: Relevance
“…Second, the model considers local populations as a homogeneous block but, in reality, community stakeholders are often more fragmented, with differences between the interests and perspectives of farmers, mining workers, contractors, and local leaders. Finally, with some adaptation, the model may be extended to analyze an emerging issue, namely, livelihood linkages between artisanal mining and farming, especially in rural African areas where, despite the economic centrality of agriculture, engagement in artisanal and small-scale mining is an off-farm diversification strategy [80]. In this case, both local economic welfare would be represented by the sum of miners' and farmers' revenues.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the model considers local populations as a homogeneous block but, in reality, community stakeholders are often more fragmented, with differences between the interests and perspectives of farmers, mining workers, contractors, and local leaders. Finally, with some adaptation, the model may be extended to analyze an emerging issue, namely, livelihood linkages between artisanal mining and farming, especially in rural African areas where, despite the economic centrality of agriculture, engagement in artisanal and small-scale mining is an off-farm diversification strategy [80]. In this case, both local economic welfare would be represented by the sum of miners' and farmers' revenues.…”
Section: Discussionmentioning
confidence: 99%
“…Although earnings in the ASM sector are considerably higher than the average income of comparable agricultural regions (Walsh, 2003;Ingram et al, 2011), it has been reported that small-scale mineral operators are unable to translate their incomes into savings and investments -two essential economic ingredients required for the sustained improvement of livelihoods (Walsh, 2003;Werthmann, 2003). Walsh (2003) refers to transient high earnings as "hot money" that fuels 'daring consumption' in the mining towns in Madagascar, although Mkodzongi and Spiegel (2019) provide a contrasting perspective with evidence that ASM-generated funds are employed for more productive purposes. The 'hot money' economic malaise has also been attributed to the mercury amalgamation processes for mineral extraction (Hilson and Pardie, 2006) and the high cost of living in ASM communities (Labonne, 2014).…”
Section: Asm As a Poverty Fightermentioning
confidence: 99%
“…They are intricate because they occupy the same geographic space and share and/or compete for the same factor inputs: land, water, labour and capital, and are dynamic because they are influenced by other exogenous factors including commodity prices (ACET, 2017b). Highlighting their synergies, a number of recent articles in development studies journals have examined the complementarities between ASM and agriculture providing evidence which point to revenues from the latter supporting the former and vice versa (Okoh and Hilson, 2011;Hilson and Garforth, 2012;Maconachie, 2011;Cartier and Bürge, 2011;Kamlongera, 2011;Mkodzongi and Spiegel, 2019;Persaud et al, 2017). Further studies have revealed that these two very important economic sectors serve as engines of employment, viable sources of income, for a majority of rural inhabitants in the developing world; (on ASM see Tschakert, 2009;Siegel and Veiga, 2010;Teschner, 2014;Kamlongera, 2011;Banchirigah, 2008) on rural agriculture see (Reardon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One important driver is the difficulty of sustaining a livelihood on the basis of smallholder agriculture (as noted by Banchirigah and Hilson 2010;Maclin et al 2017). However, as research from Sierra Leone (Maconachie and Binns 2007) and Zimbabwe (Mkodzongi and Spiegel 2019) has shown, mining does not necessarily replace farming but may co-exist with it and provide a complementary source of income. Migration patterns in mining areas also need to be understood in historical context (Cuvelier 2014;Büscher, Cuvelier, and Mushobekwa 2014) and take into account the complex nature of ASM, which may be either seasonal or permanent depending on the setting.…”
Section: Artisanal Mining and Migration In The Drcmentioning
confidence: 99%
“…The economic aspects of migration in eastern DRC are reflected in the literature on push and pull factors (Jønsson and Bryceson 2009;Hilson and Banchirigah 2009;Hinton 2011;Cuvelier, Vlassenroot, and Olin 2014;Cuvelier 2014;Grätz 2014;Hilson 2016;Maclin et al 2017;Mkodzongi and Spiegel 2019). One of the main pull factors presented in the literature is the promise of becoming "rich quickly" in the mineral sector, as an alternative to agriculture (Geenen 2011a).…”
Section: Analysing Migration: Economic Calculus and Navigating Insecumentioning
confidence: 99%